2023
DOI: 10.3390/biomedicines11041028
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Respiratory Sinus Arrhythmia and Directed Information Flow between Brain and Body Indicate Different Management Strategies of fMRI-Related Anxiety

Abstract: Background: Respiratory sinus arrhythmia (RSA) denotes decrease of cardiac beat-to-beat intervals (RRI) during inspiration and RRI increase during expiration, but an inverse pattern (termed negative RSA) was also found in healthy humans with elevated anxiety. It was detected using wave-by-wave analysis of cardiorespiratory rhythms and was considered to reflect a strategy of anxiety management involving the activation of a neural pacemaker. Results were consistent with slow breathing, but contained uncertainty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 92 publications
0
18
0
Order By: Relevance
“…In fact, negative RSA (nRSA; Rassler et al, 2018 , 2022 ) refers to the condition where increased state anxiety induces a complete reversal of the phase relationship between respiration and cardiac activity where the HR decreases during inspiration and increases during expiration. During nRSA, phase coupling analysis showed a reduced dominance of the respiratory rhythm over the RRI rhythm (see also Figure 1 ), and DTF revealed a significant information flow from RRI to respiration ( Rassler et al, 2023 ).…”
Section: Interaction Between Cardiac Rr Interval Oscillations and Bre...mentioning
confidence: 97%
See 4 more Smart Citations
“…In fact, negative RSA (nRSA; Rassler et al, 2018 , 2022 ) refers to the condition where increased state anxiety induces a complete reversal of the phase relationship between respiration and cardiac activity where the HR decreases during inspiration and increases during expiration. During nRSA, phase coupling analysis showed a reduced dominance of the respiratory rhythm over the RRI rhythm (see also Figure 1 ), and DTF revealed a significant information flow from RRI to respiration ( Rassler et al, 2023 ).…”
Section: Interaction Between Cardiac Rr Interval Oscillations and Bre...mentioning
confidence: 97%
“…A few participants displayed an increase in anxiety at the end of the sessions similar to a study reported by Chapman et al (2010) . (ii) Participants with relatively high anxiety in the first but also in a few of the last resting states displayed a high percentage of emotional breathing oscillations around 0.32 Hz ± 0.03 ( Rassler et al, 2023 ). In six subjects, eBR of about 0.32 Hz was dominant in 63–97% of the resting state epoch.…”
Section: Breathing Rate In Healthy Participants With Mri-related Anxietymentioning
confidence: 99%
See 3 more Smart Citations